Effects of Neuromuscular Electrical Stimulation on Plantarflexors Spasticity, Gait Performance, and Self-Reported Health Outcomes in People With Chronic Stroke: A Study Protocol for a Double-Blinded Randomized Clinical Trial - Almutairi, Sattam M.; Khalil, Mohamed E.; Almutairi, Nadiah; Alenazi, Aqeel M. (Frontiers in Neurology, 2021)
Introduction: Rehabilitation approaches have been used for people with stroke to decrease spasticity and improve functions, but little is known about the effect of neuromuscular electrical stimulation (NMES) in this population. Therefore, the primary purpose of this study was to establish a protocol for a double blinded-randomized clinical trial to examine using NMES on plantarflexors spasticity, dorsiflexor muscles strength, physical functions, and self-reported health outcomes in people with chronic stroke in Saudi Arabia. Material and Methods: This randomized clinical trial with two arms and double-blinded registered in ClinicalTrials (NCT04673045) will enroll 40 participants with chronic stroke and randomized them into either experimental group (EG), including electrical stimulation (ES) with conventional therapy or control sham group (NMESsham) including placebo electrical stimulation with conventional therapy. The frequency will be set at 80 Hz for 30 minutes. The intervention will be 3 times a week for 4 weeks for both groups. Data collection for pre and post intervention outcomes will include measurements for the primary outcomes including paretic limb (plantarflexor’s spasticity, ankle range of motion, and dorsiflexor muscles strength,) and gait speed using 10-Meter Walk Test (10MWT). The secondary outcomes including mobility function using Timed Up and Go (TUG), walking endurance using 6 Minutes Walk Test (6MWT), activity of daily living using the Arabic version of Barthel Index (BI), and self-reported health measures such as quality of life using Medical Outcomes Survey (SF-36), physical activity using Rapid Assessment of Physical Activity (RAPA), depression symptoms using Patient Health Questionnaire-9 (PHQ-9), fatigue level using Fatigue Severity Scale (FSS), and risk of fall using Fall Efficacy Scale International (FES-I). An independent t-test will be utilized to examine the effect of the intervention on the outcome measures. Results: The recruitment has started and is ongoing. Conclusions: Using 4 weeks of NMES will provide information about its effect in improving plantarflexor spasticity, dorsiflexor muscles strength, gait speed, mobility functions, and other self-reported health outcomes in people with chronic stroke when compared to control sham NMES.